O Programa Ensino Médio Inovador: um olhar educomunicativo na 8ª Coordenadoria Regional de Educação - Brum, Luciane da Silveira (2017)
This Master Thesis is about the area of Educational Technologies Networking for Innovation and Democratization of Education, concerning the Management of Educational Technologies Networking. The purpose of this research is the Innovative High School Program (“ProEMI”, in portuguese), instituted in 2009, as a strategy of the Government to extend the school day and the curricular organization, from the perspective of Integral Education. Integral education aims at better learning of students in public schools, through various interdisciplinary activities, including communication and digital culture. Therefore, we wonder: how does the Innovative High School Program (ProEMI) development process take place in Rio Grande do Sul, specifically in the 8th Regional Education Coordination (“CRE”, in portuguese)? How do the uses and appropriations of the media and Information and Communication Technologies (“TIC”, in portuguese) occur? The Innovative High School Program (ProEMI), which has as a paradigm a transversal Educommunicative praxis, enables the process of development of the protagonism and the emancipation of students? In order to answer these questions, we investigated the uses and appropriations of the media and the Information and Communication Technologies (TIC) in the Innovative High School Program in the state of Rio Grande do Sul, specifically in the 8th CRE, as well as the process of developing the protagonism and the emancipation of the students involved. Besides this general goal, we aimed: 1) To study the relationship between Integral Education, Innovative High School Program, Educommunication and Technological Mediation; 2) To verify the Macrofields of the Innovative High School Program, activities and results obtained in the public schools of the state of Rio Grande do Sul (8th CRE); 3) To know the main challenges and opportunities of technological mediation in the development of ProEMI. To achieve the proposed objectives, we follow five methodological steps: 1º) Exploratory research through an article of specialization produced by the researcher; 2º) State of art; 3º) Document search; 4º) Bibliographic research (MOLL, 2012; SOARES, 2002, 2011; DEMO, 2007; FREIRE, 1993; KAPLÚN, 1999; BIANCHETTI & JANTSCH, 1995); 5º) Research through the application of questionnaires with open and closed questions to the CRE's of the RS, as well as the mediating teachers of the Educommunication Project of the selected schools, belonging to the 8th CRE. Even with all the adversities observed during the ProEMI implementation and development trajectory, we find that schools are managing to create partnerships with the aim of providing integral training to their students, taking advantage of educational practices in particular. Therefore, the results of this study will be published in national and international journals so that the relevance in the treatment of the integral formation of the students can be perceived.